HUBUNGAN PERANAN OPINION LEADER (PEMUKA PENDAPAT) DENGAN TINGKAT ADOPSI PETANI DALAM BUDIDAYA SALAK PONDOH DI KECAMATAN TEMPEL KABUPATEN SLEMAN - Rosita Ningrum; Retno Setyowati; Bekti Wahyu Utami (Universitas Sebelas Maret, 2006)
Goes with Indonesia's in affords the needed of rice, intencification in agriculture could done with horticulture development that is by fruits product. This research is aimed to know the opinion leader's role toward farmer's adoption level in cultivating snake fruit var pondoh, to know farmer's adoption level and to know the correlation between opinion leader;s role with farmer's adoption level in cultivating snake fruit var pondoh. The result of analyze shows thort the opinion leader's role toward farmer 's adoption lein cultivating snake fruit var pondoh is included in middle category, where the opinion leader's role as the motivator is included in middle category, the opinion leader's role as the information source is included in high category, the opinion leader's role as the legitimator is included in high category, the opinion leader's role as the demonstrator is included in middle category. Farmer's adoption level in cultivating snake fruit var pondoh at Tempel District is included in high category, where in the seedling phase is included in high category, planting phase is included in high category, conservation phase is included in middle category, and in the harvesting phase is included in high category. The result of Rank Spearman analyza between opinion leader's role as motivator and as information source with farmer 's adoption level in cultivating snake fruit var pondoh, and there is non significant correlation between opinion leader's role as legitimator and demonstrator with farmer 'sadoption level in cultivating snake fruit var pondoh.